Effects of Vessel-Induced Waves on the Composition and Amount of Drift in an Ice Environment in the St. Marys River - Poe, Thomas P.; Edsall, Thomas A. (1982)
This study was conducted to determine how the composition and amounts of drift vary with the following conditions: 1) ice cover with vessel traffic; 2) ice cover without vessel traffic; 3) ice free with vessel traffic. Samples were taken with drift nets anchored at four locations (Brush Point, Frechett Point, Lake Nicolet, and West Neebish) in the littoral waters of the St. Marys River during January 30 - February 1, February 16-17, and March 22-23, under conditions of ice cover without vessel traffic, and on April 29 - May 1, under ice free conditions with vessel traffic. Samples were also taken at these four locations and with drift nets towed in the navigation channel during April 29 - May 1 under the ice free conditions with vessel traffic. Keywords: Ice cover; Vessel traffic; Ice free drift nets. (JHD)